Chapter Two: The Weight of Past Historiography and the State of the Question: The Revelations of Pierre de La Place and Louis Regnier de La Planche. - Benedict, Philip (Transactions of the American Philosophical Society, 2020)
36 SEASON OF CONSPIRACY Was Regnier covering up for him here, as he may also have been when he chose to identify the captain of the conspiracy for Champagne and the Ile-de-France only by the letter "N "? Meanwhile, arch-Catholic historians from Saconay and Le Frere de Laval through the author of the 1579 Grancles annales et histoire generale de France, Francois de Belleforest, to the important seven- teenth-century historian Scipion Dupleix (1569-1661) offered a very different picture of the conspiracies, their key actors, and their motives. According to La Planche, the elder Maligny had not been involved in the Amboise conspiracy but was nonetheless summoned to court to answer for a role that was improperly attributed to him. Whatever the accuracy of La Planche's claim about the elder Maligny's prior innocence, it was his summons to court, La Planche explains, that led the Burgundian nobleman to realize that he needed to protect himself.